Analisis Startegi Bauran Promosi Batik Besemah Kota Pagaralam - Dimyati, Laili (Universitas muhammadiyah palembang, 2017)
This study aims to determine the promotion mix strategy of Batik Besemah based on the strengths, weaknesses, opportunities, and threats which are owned by the product of Batik Besemah and formulate appropriate promotion mix strategy used after analyzed using SWOT analysis. Types of research used in this research is descriptive researchwith a focus on internal and external environment, and then to formulate a strategy, then processed into several stages, analyze internal and external environmental conditions and then using SWOT Matrix. The results showed that the strength of promotion mix Batik Besemah is exhibition, telephone marketing, and good cooperation with external parties. The weaknesses of the promotion mix is the limited budget and independent business. The opportunities that can be utilized is advertising and online marketing, lobbying government policies, proposing cooperation and expanding the market. The threats is the presence of competitors and market characteristics in Pagar Alam town.